Pengaruh Perencanaan Pajak, Kebijakan Dividen Dan Corporate Social Responsibility Terhadap Nilai Perusahaan - Gunung Subagyo Anom Haryoso (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to examine the effect of tax planning, dividend policy, and corporate social responsibility on firm value in the consumer non-cyclical sector for the years 2018-2022. The research uses a quantitative method with secondary data sources. The research population consists of companies in the consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022, totaling 113 companies. The sample selection technique uses purposive sampling, resulting in 20 companies meeting the criteria. Data analysis techniques are conducted with the aid of MS Excel and Eviews version 12, with analytical steps including descriptive statistical tests, panel data selection tests, classical assumption tests, and hypothesis testing. The research results show that tax planning does not affect firm value, dividend policy does not affect firm value, while corporate social responsibility affects firm value.